Interim Leadership Positions: The Kobayashi Maru of Academia? - Alisha Ortiz; Julie A. Ray; Victor R. Wilburn; Melissa Odegard-Koester; Jeremy Ball (Academic Chairpersons Conference Proceedings, 2019)
Leading a department through a transition such as reorganization or restructuring is difficult. When the unit leader is in an interim position, this is even more complicated. This presentation will be led by faculty who were all in interim leadership positions during major transitions in leadership, restructuring, and staff layoffs.
Keywords: Managing Change; Leadership; Transition; Academic Restructuring; Conflict